Hubungan Kebiasaan Konsumsi Masakan Padang dengan Kadar Kolesterol (Studi pada Paguyuban Ikatan Mahasiswa Minang Angkatan 2015 di Semarang) - Nur Asiah Rahmi; Muhammad Zen Rahfiludin; Dina Rahayuning Pangestuti (Jurnal Kesehatan Masyarakat (Undip), 2017)
High cholesterol blood level can form a sediment on the blood vessel wall. Cholesterol can harm the body when consumed in an excessive amount. Increased cholesterol in blood is called hypercholesterolaemia. The purpose of this research was to analyze the correlation of Padang food consumption habit with cholesterol level in IKAMMI community Semarang. This is a quantitative research with cross sectional design with population of 82 people. Samples of this research were 45 people. Sampling technique in this research was using simple random sampling. The correlation trial was using rank spearman. The results showed that frequency of padang food consumption habit was often (75,6%), fat consumption was low (80%), knowledge’s level was adequate (73,3%), percentage of body fat was normal (31,1%) and  percentage of body fat was overweight (31,1%), physical activity was moderate (48,9%) and cholesterol level was optimal (73,3%).  There were significant correlations of food habit (p value= 0,024), fat consumption (p value= 0,01)  and percentage of body fat ( p value = 0,046) with cholesterol level. There were no correlations of knowledge’s level (p value= 0,979) and physical activity (p value= 0,439) with cholesterol level. This research recommended eating habit of college student should be more regulated and they need to reduce fatty food in order to keep the cholesterol in normal level and also increasing physical activity because high physical activity can reduce fat and cholesterol level.